Between royal orbits: jurisdiction in the Northern British Isles ca 1100–1360. Issue 1 (2nd January 2017) - Grohse, Ian Peter
Abstract : This article studies the role of international treaties in defining jurisdiction and managing conflicts in the maritime space around Scotland in the central and late Middle Ages. Beginning with the first known Norwegian-Scottish agreement from 1098, this investigation emphasises discrepancies between the initial principle of jurisdictional exclusivity and the practical enforcement of legal authority over islands and waterways along Scotland's Western and Northern seaboards. In doing so, it emphasises the weakness of royal authority and the importance of non-institutional and private strategies for protecting merchants and mariners prior to the late-thirteenth century. The resolution of a military conflict over control of the Hebrides in 1266 compelled more finite demarcations of jurisdiction and binding obligations to maintain order along kings' common jurisdictional frontier. From this basis, late-medieval rulers cooperated more effectively in resolving conflicts between their subjects in the maritime space.